Microbial Derived Compounds, a Step Toward Enhancing Microbial Inoculants Technology for Sustainable Agriculture - Naamala, Judith; Smith, Donald L. (Frontiers in Microbiology, 2021)
Sustainable agriculture remains a focus for many researchers, in an effort to minimise environmental degradation and climate change. The use of plant growth promoting microorganisms (PGPM) is a hopeful approach for enhancing plant growth and yield. However, the technology faces a number of challenges, especially inconsistencies in the field. The discovery, that microbial derived compounds can independently enhance plant growth, could be a step towards minimising shortfalls related to PGPM technology. This has led many researchers to engage in research activities involving such compounds. So far, the findings are promising as compounds have been reported to enhance plant growth under stressed and non-stressed conditions in a wide range of plant species. This review compiles current knowledge on microbial derived compounds, taking a reader through a summarised protocol of their isolation and identification, their relevance in present agricultural trends, current use and limitations, with a view to giving the reader a picture of where the technology has come from, and an insight into where it could head, with some suggestions regarding the probable best ways forward.